Empowering Students: Evaluating the Impact of Career Education Programs on College Major Choices - Oskar, Oskar; Simbolon, Rempi; Kondar, Kondar; Sinaga, Marzan (Jurnal Ilmu Pendidikan dan Humaniora, 2022)
The selection of a college major represents a pivotal decision in the lives of students, shaping their academic and professional futures. Amid the ever-expanding array of academic disciplines and the challenges of navigating career aspirations, career education programs emerge as essential tools in empowering students to make informed choices. This research endeavors to assess the effectiveness of career education programs in aiding students with their major decisions and illuminates the significance of their impact. Through a comprehensive examination that included surveys, interviews, and data analysis, the study offers insights into the transformative potential of career education programs. The findings underscore the positive influence of these programs on students' major choices and career aspirations. Students who engage with career education programs consistently make choices that align with their passions and goals. The study also highlights the pivotal role of these programs in nurturing self-confidence among students in making major decisions, instilling in them the belief that they possess the ability to shape their own academic and professional destinies. Moreover, the research acknowledges demographic variations in the effectiveness of these programs. Differences in program impact among various student groups, such as gender and socioeconomic status, underscore the importance of inclusive and targeted approaches to program design and implementation. The implications of these findings are profound, extending across the educational landscape. They emphasize the significance of equitable access to career education programs, call for resource allocation decisions that support the investment in these programs, and advocate for policy measures that recognize the pivotal role of career education in student success.